Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1200/jco.1986.4.12.1732
|View full text |Cite
|
Sign up to set email alerts
|

Results of treatment of advanced-stage Burkitt's lymphoma and B cell (SIg+) acute lymphoblastic leukemia with high-dose fractionated cyclophosphamide and coordinated high-dose methotrexate and cytarabine.

Abstract: To address the problem of historically poor results in the treatment of children with advanced-stage Burkitt's lymphoma and B cell (SIg+) acute lymphoblastic leukemia (ALL), an intensive chemotherapy regimen was devised using the most effective single agents in high-dose short courses. Treatment commenced with a fractionated schedule of intravenous (IV) cyclophosphamide (300 mg/m2 every 12 hours for six doses) followed immediately by Adriamycin (50 mg/m2) and vincristine (1.5 mg/m2) with combined intrathecal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
96
1
4

Year Published

1987
1987
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(105 citation statements)
references
References 10 publications
4
96
1
4
Order By: Relevance
“…However, the authors observed that patients older than 60 years clearly had an inferior outcome, with a survival rate of only 17% [9]. The addition of Rituximab and the improvement in supportive care measures possibly contributed to the achievement of similar outcomes in older and younger adults [10].In 1997, we reported a monocentric experience of 21 patients (8 adults and 13 children) treated with the intensive short-term pediatric-derived chemotherapy regimen POG 8617 [11], demonstrating that the outcome in adults was not significantly different than in children [12]. Fourteen years after our original report, we present here the longterm results of the same chemotherapy regimen employed in a multicenter experience recruiting a larger cohort of 71 consecutive BL patients.…”
mentioning
confidence: 99%
“…However, the authors observed that patients older than 60 years clearly had an inferior outcome, with a survival rate of only 17% [9]. The addition of Rituximab and the improvement in supportive care measures possibly contributed to the achievement of similar outcomes in older and younger adults [10].In 1997, we reported a monocentric experience of 21 patients (8 adults and 13 children) treated with the intensive short-term pediatric-derived chemotherapy regimen POG 8617 [11], demonstrating that the outcome in adults was not significantly different than in children [12]. Fourteen years after our original report, we present here the longterm results of the same chemotherapy regimen employed in a multicenter experience recruiting a larger cohort of 71 consecutive BL patients.…”
mentioning
confidence: 99%
“…[3][4][5] Once a patient relapses or fails to achieve a complete remission, salvage chemotherapy regimens have been reported to have reinduction rates of 20-60%, but, nevertheless, median CR remission duration averages only 3.4 months. 6 Over a period of 44 months, 66 patients at our institution were given salvage chemotherapy with the 'hyper-CVAD' regimen, a dose-intensive regimen patterned after the childhood Burkitt ALL therapy designed by Murphy et al 7 We called the regimen 'hyper-CVAD' after the acronym for the initial induction combination. 8 Our findings are summarized in this report.…”
Section: Introductionmentioning
confidence: 99%
“…11 With the current chemotherapy regimens, the overall cure rates are approximately 90% in children and 50% to 60% in adults. [12][13][14][15] However, patients with high-stage disease continue to have a less favorable prognosis, with cure rates of 80% to 85% in children 15 and 40% to 50% in adults 16 There are no known biological tumor features that reliably predict the behavior of BL. In addition, it is not entirely clear if the difference in outcome between children and adults is a result of a relatively poor tolerance to treatment in the latter or if it is at least partially attributable to differences in tumor biology.…”
mentioning
confidence: 99%